2018
DOI: 10.15694/mep.2018.0000077.1
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Public Health in Medical Education Training

Abstract: Since the implementation of the current Brazilian Health System (Sistema Único de Saude -SUS), there has been a trend to change medical school curricula regarding primary care and community-centered activities, in an attempt to replace the predominant hospital-centered teaching model, and to graduate more general practitioners. The current national guidelines for medical schools' curricula support this orientation; however, many medical schools present with difficulties to change their curricula, especially co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Concerning the public health curriculum, a qualitative study was conducted in Brazil to investigate the importance of public health in the education of medical students ( 46 ). Results revealed that students regarded public health as essential to their medical education and professional roles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the public health curriculum, a qualitative study was conducted in Brazil to investigate the importance of public health in the education of medical students ( 46 ). Results revealed that students regarded public health as essential to their medical education and professional roles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those who emphasized public health more in their studies reported higher levels of satisfaction and proficiency in various aspects of public health-related work. The study suggested incorporating public health more deeply, starting early, and prioritizing practical activities to stimulate interest and attract more students ( 46 ). Similarly, a mixed-methods study examined the knowledge, attitudes, and perceptions of fifth-year medical students at South African University regarding their public health course to inform the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a large amount of research and several reports have been conducted on this issue. The findings were mostly reported in a quantitative form, which could neglect the economic backgrounds, human factor consideration, in-depth understanding, and core sharing [17].…”
Section: Introductionmentioning
confidence: 99%